Low-Dose Acetylsalicylic Acid Use and the Risk of Upper Gastrointestinal Bleeding: A Meta-Analysis of Randomized Clinical Trials and Observational Studies. (2013) - Valkhoff, Vera E; Sturkenboom, Miriam CJM; Hill, Catherine; Veldhuyzen van Zanten, Sander; Kuipers, Ernst J
Abstract : BACKGROUND: Low-dose acetylsalicylic acid (LDA, 75 mg/day to 325 mg/day) is recommended for primary and secondary prevention of cardiovascular events, but has been linked to an increased risk of upper gastrointestinal bleeding (UGIB). OBJECTIVE: To analyze the magnitude of effect of LDA use on UGIB risk. METHODS: The PubMed and Embase databases were searched for randomized controlled trials (RCTs) reporting UGIB rates in individuals receiving LDA, and observational studies of LDA use in patients with UGIB. Studies were pooled for analysis of UGIB rates. RESULTS: Eighteen studies were included. Seven RCTs reported UGIB rates in individuals randomly assigned to receive LDA (n=22, 901) or placebo (n=22, 923). Ten case-control studies analyzed LDA use in patients with UGIB (n=10, 816) and controls without UGIB (n=30, 519); one cohort study reported 207 UGIB cases treated with LDA only. All studies found LDA use to be associated with an increased risk of UGIB. The mean number of extra UGIB cases associated with LDA use in the RCTs was 1.2 per 1000 patients per year (95% CI 0.7 to 1.8). The number needed to harm was 816 (95% CI 560 to 1500) for RCTs and 819 (95% CI 617 to 1119) for observational studies. Meta-analysis of RCT data showed that LDA use was associated with a 50% increase in UGIB risk (OR 1.5 [95% CI 1.2 to 1.8]). UGIB risk was most pronounced in observational studies (OR 3.1 [95% CI 2.5 to 3.7]). CONCLUSIONS: LDA use was associated with an increased risk of UGIB.